2020
DOI: 10.1259/dmfr.20190468
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of national diagnostic reference levels in dental cone beam computed tomography in Switzerland

Abstract: Objectives: The aim of this study was to establish diagnostic reference levels (DRLs) in the field of dental maxillofacial and ear-nose-throat (ENT) practices using cone beam CT (CBCT) in Switzerland. Methods: A questionnaire was sent to owners of CBCTs in Switzerland; to a total of 612 institutions. The answers were analyzed for each indication, provided that enough data were available. The DRLs were defined as the 75th percentile of air kerma product distribution (PKA). Results: 227 answers were collected (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…However, very few countries currently have established national DRLs in dental CBCT imaging (Table 3, see also [58] for a general discussion on optimisation and DRLs). Switzerland published their national DRLs for five dental indications [59] as did Finland for four dental or maxillofacial indications [60] and Sweden for three non-indication-based examinations in the dental region [61]. In the UK, Public Health England has suggested DRLs both for a specific adult and child CBCT protocol [62].…”
Section: Diagnostic Reference Levelsmentioning
confidence: 99%
“…However, very few countries currently have established national DRLs in dental CBCT imaging (Table 3, see also [58] for a general discussion on optimisation and DRLs). Switzerland published their national DRLs for five dental indications [59] as did Finland for four dental or maxillofacial indications [60] and Sweden for three non-indication-based examinations in the dental region [61]. In the UK, Public Health England has suggested DRLs both for a specific adult and child CBCT protocol [62].…”
Section: Diagnostic Reference Levelsmentioning
confidence: 99%
“…Finally, due to the growing use of CBCT imaging [18][19][20], it is critical that its advantages and disadvantages are carefully evaluated, especially in the areas of radiation doses to patients and economic costs. Notably, the cost of CBCT imaging for assessment of impacted third molars is approximately four times higher [4], and the radiation dose, many times higher, than that for a panoramic radiograph [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon has been reported from Switzerland, yet panoramic imaging was still regarded as the reference investigation in dentistry. Nevertheless, it was found that wisdom teeth were the most common indication for CBCT [ 19 ]. Another study in the USA [ 20 ] investigated the use of CBCT in imaging of impacted teeth among other indications in oral and maxillofacial surgery and found an overall trend of using CBCT instead of panoramic imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important aspects raised by the literature that could be important in the current pandemic is the establishment of faster, safer and optimal imaging diagnostic protocols 18 . For this purpose, imaging diagnostic centers should have adequate equipment hardware to perform faster scans, as well as to store and send images digitally to the responsible clinician, avoiding generation of printed exams.…”
Section: Oral and Maxillofacial Radiologymentioning
confidence: 99%